Removal of Heavy Metals Using Adsorbents at Low Cost: Effective and Affordable Methods for Heavy Metal Removal from Industrial Wastewater (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The heavy metals discharged in industrial waste water are having toxic properties and may become harmful for biotic environment, animals humans. Due to a variety of industrial processes these heavy metals are released into the environment by industrial waste water. Some of the industries like battery, mining, electroplating, electronic equipments, etc. use Lead, Zinc, Nickel, Cadmium, Chromium and Copper heavy metals which are having the acute toxic nature. These heavy metals impart various detrimental health and environmental effects due to their presence in waste water. The removal of heavy metal ions from wastewater is critical for environmental and human health reasons. Heavy metal ions were removed from various wastewater sources using various documented procedures. Treatments based on adsorption, membranes, chemicals, electricity, and photo catalysis are among the options.